A comparison of two different technologies tools in tutoring calculus - Mohd Ayub, Ahmad Fauzi; Mokhtar, Mohd Zin; Wong, Su Luan; Ahmad Tarmizi, Rohani (Elsevier, 2010)
Educational technology is used to increase the efficiency of education in educational settings. Computers and related technology are viewed as the future of teaching and learning and also as a powerful technological machine to promote development of learning. There are many researches that have been conducted using computer technology in teaching and learning mathematics. However, the findings of these researches are not consistent. This paper will discuss the effectiveness of using two different types of computer technology on the achievement of students in Calculus. Specifically, this paper will discuss the effectiveness of SAGE, MACCC and traditional tutorial approach on the achievement of diploma students in the topic of limit. This research is a quasi-experimental research involving students from three groups assigned to a control group (28 students), SAGE group (24 students) and MACCC group (23 students). The SAGE and MACCC groups are defined as two treatment groups. The statistical analysis revealed that there is a statistically significant difference between students’ achievement in the control, MACCC and SAGE groups. Findings indicate that students using computers have better performance compared to control group. However, there is no significant difference between SAGE and MACCC group. This research implies that computer could be used as a tool in teaching and learning calculus especially during tutorial class.